Literatura popularna jako źródło wiedzy specjalistycznej. Leksyka medyczna w serii "Medical Romance" = Popular literature as a source of specialist knowledge. Medical lexicon in the "Medical Romance" series - Gorzelana, Joanna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The purpose of the text is to present a medical lexicon in selected books from the "Harlequin Medical" series. To achieve this, I used the semantic fields method, namely, the terms naming diseases (e.g. leukemia, diabetes, appendicitis), treatment or diagnosis (surgery, catheterisation, blood analysis), medicines (e.g. insulin, saline, gammaglubulin), people (e.g. paediatrician, paramedic, patient) and places (e.g. clinic, hospital, operating room) were isolated and identified. Quantitative analysis of the texts shows that the lexicon related to medicine is extensive and can be a source of specialist knowledge. Medical themes in this series dominated matters related to feelings and eroticism.
Keywords: literatura popularna; medycyna; romans; słownictwo; popular literature; medicines; romance; vocabulary